Non‐completion of latent tuberculosis infection treatment among Vietnamese immigrants in Southern California: A retrospective study. Issue 6 (7th September 2020) - Nguyen Truax, Fayette; Morisky, Donald; Low, Julie; Carson, Michael; Girma, Haimanot; Nyamathi, Adeline
Abstract: Objectives: To examine socio‐demographic and health‐related factors associated with latent tuberculosis infection (LTBI) treatment refusal, non‐initiation, and non‐completion among a cohort of Vietnamese immigrants. Design: This is a retrospective cohort study in which LTBI charts were reviewed at a public health clinic in Orange County, California between January 2010 and August 2011. Sample: Altogether, 474 patient charts with documented LTBI treatment were reviewed for patients who met the inclusion criteria. Measurements: Univariate and multivariate analyses were used to identify socio‐demographic and health‐related factors associated with LTBI treatment refusal, non‐initiation, and non‐completion. Results: Of the 474 charts reviewed, 171(36.1%) patients refused LTBI treatment and 21(6.9%) accepted but did not initiate. Of the 282 that started treatment, 62 (22.0%) did not complete the regimen prescribed. The primary barrier documented for treatment refusal and non‐completion was concern about medication side effects. Other barriers to treatment non‐completion include transportation issues and conflicts with travel plans or work schedules. Conclusions: Community and public health nurses working with the Vietnamese immigrant population can play a vital role in improving patients' LTBI treatment acceptance, initiation, and completion. A proactive approach to addressing barriers and potential medication side effects can improve overall treatment success.